Temporal Artery Temperature Measurement in the Neonate - Syrkin-Nikolau, Mashette E.; Johnson, Karen J.; Colaizy, Tarah T.; Schrock, Ruthann; Bell, Edward F. (American Journal of Perinatology, 2017)
Objective We compared an infrared temporal artery thermometer with our clinical standard axillary thermometer for temperature measurements in neonatal patients.Study Design We measured temporal artery (Tta), axillary (Tax, clinical standard), and rectal (Tr, gold standard) temperatures of 49 infants. The difference between Tr and Tta was compared with that between Tr and Tax, and the data were analyzed based on bed type and postmenstrual age.Results The mean Tta, Tax, and Tr were 37.16 (SD 0.36) °C, 36.61 (SD 0.30) °C, and 36.82 (SD 0.30) °C, respectively. The measurements by these methods were all significantly different. The mean Tr-Tax was 0.21 (SD 0.26) °C, and the mean Tr-Tta was −0.34 (SD 0.37) °C, indicating that Tax was closer to Tr than was Tta (p < 0.0001). Tta agreed more closely with Tr for infants in cribs than for those in incubators. Adjusting for bed type and body weight, with each week of postmenstrual age, the discrepancy between Tr-Tta and Tr-Tax decreased by 0.005°C (p = 0.034).Conclusion Compared with the gold standard, Tr, Tta is not more accurate than Tax. The temporal artery thermometer was less accurate for infants in incubators than for infants in cribs. The accuracy of temporal artery temperature increased with postmenstrual age.
Keywords: temporal artery temperature; axillary temperature; rectal temperature; neonate; infant